Incidence and predictors of subacute thrombosis in patients undergoing primary angioplasty for an acute myocardial infarction - Smit, Jaap Jan J.; van ’t Hof, Arnoud W. J.; de Boer, Menko Jan; Hoorntje, Jan C. A.; Dambrink, Jan Henk E.; Gosselink, A. T. Marcel; Ottervanger, Jan Paul; Kolkman, J. J. Evelien; Suryapranata, Harry (Thrombosis and Haemostasis, 2006)
Subacute thrombosis (SAT) is a major concern in patients undergoing percutaneous coronary intervention (PCI). So far, only little data has been available on characteristics and outcome of patients with SAT after primary PCI for ST elevation myocardial infarction (STEMI). From 1997–2001, 1,548 unselected consecutive patients underwent primary PCI for STEMI as part ofa randomized controlled trial stenting vs. balloon angioplasty. All patients received acetylsalicylic acid (500 mg i. v.) and heparin (5,000 IU) before the procedure. After stenting, all patients received ticlopidine 250 mg daily (before July 1999) or clopidogrel 75 mg daily (after July 1999) for one month. Five percent of patients received glycoprotein IIb/IIIa blockers. We prospectively recorded incidence and characteristics of patients with SAT during one year follow-up. SAT occurred in 4. 1% (63/1548) and reinfarction in 6. 0% of patients. The incidence of SAT did not change over time (1997: 8/175[4. 6%],1998: 8/325 [2.5%],1999: 13/358 [3.6%], 2000: 22/426 [5.2%], 2001: 12/264 [4.5%]). SAT occurred in 39/63(62%) patients during hospital stay. The incidence did not differ between patients after ticlopidine 23/681 (3.4%) or clopidogrel 40/867 (4. 6%, p=0. 222). Univariate predictors of SAT were: patients with an LAD stenosis (5.4% vs. 2.9%, p=0. 016), with Killip class>1 at presentation (8.6% vs. 3.7%, p=0.007) and in patients who received a stent (5.1% vs. 2.7%, p=0. 022). After multivariate analysis, Killip class>1 on admission was the only independent predictor of SAT(OR 2.26, 95% CI 1.14–4.47, p=0.019). SAT was associated with a higher mortality at long-term follow-up (15% vs. 7%, p=0. 026). In a prospectively recorded, unselected consecutive series of patients undergoing PCI for STEMI, SAT occurred in 4. 1% of patients at oneyear follow-up. Signs of heart failure on admission, anterior myocardial infarction and stenting were predictors of SAT.
Keywords: Subacute thrombosis; catheterization; STEMI; prognosis; PCI